1995
DOI: 10.1590/s0103-90161995000200014
|View full text |Cite
|
Sign up to set email alerts
|

Indução de mutação visando a redução de altura de planta e resistência às doenças no cultivar de trigo (Triticum aestivum L.) IAC-17

Abstract: RESUMO: A redução na altura da planta e obtenção de resistência às doenças foi experimentada através da indução de mutação por raios-gama na variedade de trigo (Triticum aestivum L.) IAC-17. Sementes foram irradiadas com 35 krad e a partir da geração M 2 iniciou-se a seleção. Três das linhagens selecionadas foram comparadas com o cultivar original IAC-17, durante três anos, em sete ensaios avançados realizados em vários locais, em condição de sequeiro e irrigação. Os resultados demonstraram a obtenção de um mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Similar results were reported by Camargo & Oliveira (1981a), studying BH-1146 under non-limiting nutrient level, Alfree, pH 4.0 solution who reported a higher potential for root growth in these plants, evidencing their specificity for this trait. The use of gamma radiation in seeds of some wheat cultivars generated plants with specific agronomic characteristics, such as tolerance to Al, usually present in acidic soils (Camargo et al, 1997;Tulmann Neto et al, 1995a;1995b;1996 and2001). Most of the published research on this subject has been done in the presence of Al 3+ and has shown that in the wheat early development stages, root growth is affected by temperature, pH, salts and phosphorus concentrations of the nutrient solutions (Ali, 1973;Camargo & Oliveira, 1981a;Camargo, 1983;1984;Moore, 1974;Moore et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by Camargo & Oliveira (1981a), studying BH-1146 under non-limiting nutrient level, Alfree, pH 4.0 solution who reported a higher potential for root growth in these plants, evidencing their specificity for this trait. The use of gamma radiation in seeds of some wheat cultivars generated plants with specific agronomic characteristics, such as tolerance to Al, usually present in acidic soils (Camargo et al, 1997;Tulmann Neto et al, 1995a;1995b;1996 and2001). Most of the published research on this subject has been done in the presence of Al 3+ and has shown that in the wheat early development stages, root growth is affected by temperature, pH, salts and phosphorus concentrations of the nutrient solutions (Ali, 1973;Camargo & Oliveira, 1981a;Camargo, 1983;1984;Moore, 1974;Moore et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, a point mutation can correct or improve some traits, allowing the selection of superior genetic constitutions in the early generations. This strategy was used to change the frequency of some genes that are negligible by the expression of traits in the IAC-24 wheat cultivar, allowing the selection of at least eight lines that maintained the original characteristics and had traits such as the height of plants and tolerance to pathogens (Tulmann-Neto et al, 1995). In triticale, mutation induction was efficient in reducing the height of plants like those produced by artificial crosses (Pandini et al, 1997).…”
Section: Mutant Studymentioning
confidence: 99%
“…Novos trabalhos coordenados pela Agência Internacional de Energia Atômica, Áustria, foram iniciados em 1985. Nessa época, sementes de algumas cultivares de destaque foram irradiadas visando à melhoria de algumas características agronômicas específicas, dentre elas a tolerância ao alumínio tóxico presente em solos ácidos (TULMANN-NETO et al, 1995;CAMARGO et al, 1997).…”
Section: Introductionunclassified